2008
DOI: 10.5194/acp-8-2999-2008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aircraft and satellite measurements from the Intercontinental Chemical Transport Experiment (INTEX-B) to quantify long-range transport of East Asian sulfur to Canada

Abstract: Asian sulfate over the ocean is in the lower free troposphere (800-600 hPa), with a decrease in pressure toward land due to orographic effects. We calculate that 56% of the measured sulfate between 500-900 hPa over British Columbia is due to East Asian sources. We find evidence of a 72-85% increase in the relative contribution of East Asian sulfate to the total burden in spring off the northwest coast of the United States since 1985. Campaign-average simulations indicate anthropogenic East Asian sulfur emissio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
201
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 257 publications
(215 citation statements)
references
References 77 publications
(81 reference statements)
14
201
0
Order By: Relevance
“…However, simultaneous observation for dust-laden aerosols between the boundary layer and the free troposphere has been conducted only in the Asian continental outflow region such as the ACE-Asia 2001 in Northwest Pacific (Huebert et al, 2003;Seinfeld et al, 2004;Simoneit et al, 2004a, b) and the INTEX-2006 in Northeast America Peltier et al, 2008;van Donkelaar et al, 2008), but there is no such a simultaneous measurement conducted in inland China. Located in central China, Guanzhong Basin is one of the most polluted regions in the world, where the annual average level of fine particles was more than 80 µg m −3 in 2001(van Donkelaar et al, 2010Wang et al, 2006aWang et al, , b, 2010. In the spring of 2009, an intensive observation of atmospheric aerosols was performed simultaneously in Xi'an (109 • 39 E,34 • 45 N), Mt.…”
Section: G H Wang Et Al: Impact Of Gobi Desert Dust On Aerosol Chementioning
confidence: 99%
“…However, simultaneous observation for dust-laden aerosols between the boundary layer and the free troposphere has been conducted only in the Asian continental outflow region such as the ACE-Asia 2001 in Northwest Pacific (Huebert et al, 2003;Seinfeld et al, 2004;Simoneit et al, 2004a, b) and the INTEX-2006 in Northeast America Peltier et al, 2008;van Donkelaar et al, 2008), but there is no such a simultaneous measurement conducted in inland China. Located in central China, Guanzhong Basin is one of the most polluted regions in the world, where the annual average level of fine particles was more than 80 µg m −3 in 2001(van Donkelaar et al, 2010Wang et al, 2006aWang et al, , b, 2010. In the spring of 2009, an intensive observation of atmospheric aerosols was performed simultaneously in Xi'an (109 • 39 E,34 • 45 N), Mt.…”
Section: G H Wang Et Al: Impact Of Gobi Desert Dust On Aerosol Chementioning
confidence: 99%
“…For high values, denitrification dominates preferentially emitting N 2 O and N 2 ; diffusion of emitted gases through the soil pores is also limited. S NO x dependence on soil moisture is thus best described as a Poisson function Otter et al, 1999;Pierce and Aneja, 2000;Kirkman et al, 2001;van Dijk and Meixner, 2001; van Dijk et al, 2002) where the values of a and b are chosen such that the maximum value (unity) occurs for θ = 0.2 for arid soils and 0.3 elsewhere. Laboratory and field measurements have found that emissions peak in this range for most soils (Yang and Meixner, 1997;Ormeci et al, 1999).…”
Section: Soil Moisture/soil Temperature Dependencementioning
confidence: 99%
“…CO emissions from combustion amount to 858 Tg a −1 , with an additional 140 Tg a −1 from oxidation of co-emitted NMVOCs. They are drawn from EDGAR 3.2FT2000 inventory (Olivier et al, 1999;Olivier and Berdowski, 2001) for the year 2000, implemented in GEOS-Chem by van Donkelaar et al (2008). These are overwritten with the following regional inventories: the US Environmental Protection Agency National Emission Inventory for 1999 (EPA-NEI99) for the US with a 60% downward correction following Hudman et al (2008) (NEI99 Hudman), the Big Bend Regional Aerosol and Visibility Observational (BRAVO) Study Emissions Inventory for Mexico (Kuhns et al, 2003) .…”
Section: Co Simulation In the Geos-chem Ctmmentioning
confidence: 99%